Is it possible to age safely by practicing ultra-endurance exercises? (PerCursos, 2023)
The healthy aging process undoubtedly includes having a lifestyle with positive choices and habits. In this context, the practice of physical exercise. It is well established that moderate-intensity physical exercise collaborates to reduce morbidities and loss of functionality of different physiological systems, as well as decreases the risk of orthopedic and cardiovascular disorders associated with aging. However, the performance of physical exercises of high intensity and volume, such aerobic ultra-resistance (IronMan triathlon, marathon, road cycling, etc.) in the presence of congenital and/or acquired cardiovascular diseases can predispose practitioners to an increased risk of sudden death. In addition, there is disagreement in the scientific literature as to whether the practice of ultra-resistance exercises during the aging process is safe for health and can increase or decrease longevity. Thus, the aim of this opinion article is to discuss the current literature on the subject from the perspective of the question “Is it possible to age safely by practicing ultra-endurance exercises?” as well as the possible association of this type of physical exercise with cases of sudden death. Our research shows that despite the benefits of physical exercise, high-intensity exercise combined with pre-existing health conditions can be the trigger for sudden death events.
Keywords: aging; health; physical exercise; sudden death; physical activity